IMPLEMENTASI MODEL ADDIE DAN KOMPETENSI KEWIRAUSAHAAN DOSEN TERHADAP MOTIVASI WIRAUSAHA MAHASISWA - Sari, Indah Purnama (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2018)
The purpose of this study is to determine the effect of the implementation of ADDIE model and entrepreneurship competence of lecturers to student entrepreneur motivation, either partially or simultaneously. Samples were taken by a total of 30 people at random from 2 different classes who had taken entrepreneurship courses. Data were collected using questionnaires. Data then analyzed by quantitative method that is multiple linier regression analysis. Based on the classical assumption test, no classical assumption problem was found in the regression model. Based on the result of t test, it is found that implementation variable of ADDIE model has no significant effect to entrepreneurship motivation of student, while entrepreneurship entrepreneur competence variable has significant effect to entrepreneurship motivation of student. The results of the F test showed that both independent variables together significantly influence the entrepreneurial motivation. Based on R2 test shows the contribution of variable implementation of ADDIE Model and entrepreneurship competence of lecturer, small on variable entrepreneur motivation in student. Recommendations based on the results of research is that universities need to consider aspects of entrepreneurship competence of lecturers in terms of assigning lecturers of entrepreneurship subjects